AN ANALYSIS OF THE QUALITY INFLUENCING THE DIVERSIFICATION MECHANISM IN TOURISM ASSISTANCE (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This comprehensive analysis delves into the intricate relationship between quality and the diversification mechanism in tourism assistance. The study examines how the quality of services, particularly in customer experience, service delivery, and technological integration, significantly influences the diversification of the tourism sector. High-quality tourism assistance, which includes elements like personalized services, use of advanced digital platforms, and the adoption of virtual reality (VR) tours, enables destinations to cater to various segments of the market. By providing tailored experiences, tourism assistance can attract new types of tourists, thereby broadening the market base.The analysis also emphasizes the importance of cultural authenticity and sustainability in tourism. Offering genuine cultural experiences, supporting local businesses, and integrating eco-friendly practices not only enhance the quality of services but also attract niche markets such as eco-tourists and culture enthusiasts. Diversification is further encouraged by promoting local culture, traditions, and art through tourism assistance, which helps ensure that tourism growth benefits various sectors of the local economy.Another critical factor in tourism diversification is the quality of training and development for tourism professionals. Skilled staff who are well-versed in customer service, cross-cultural communication, and specialized knowledge, such as local history or environmental conservation, improve the overall quality of services provided. This enables tourism assistance services to cater to a broader and more diverse audience, including international tourists, families, and senior travelers, thus expanding the tourism sector.Key words: Digitalization of tourism, Technological infrastructure, Government initiatives, Digital transformation, Digital literacy, Virtual tours, Visitor expectations, Online booking platforms.